Peran Yayasan SPEK-HAM Dalam Pencegahan Dan Pemulihan Korban Kekerasan Seksual Di Kota Surakarta - Farahavisa Rifastya Mahfud; Subekti Subekti; Riska Andi Fitriono (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Sexual violence is a serious problem that causes physical and psychological harm to the victims. In efforts to prevent and address sexual violence, cooperation from all elements of society is very much needed, including through community-based service provider organizations as a form of community participation. This is regulated in Indonesian Law on Sexual Violence, Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (UU TPKS) Article 85 regarding Community Participation, both in prevention and victim recovery. The Solidarity Foundation for Women's Humanity and Human Rights (SPEK-HAM) in Kota Surakarta is one of the community-based service provider organizations that play an important role in providing various prevention and victim recovery programs in accordance with the mandate of Indonesian Law on Sexual Violence (UU TPKS). However, in its implementation, SPEK-HAM faces various internal and external obstacles in fulfilling its role as a community-based service provider organization. This study uses the empirical legal research method to analyze SPEK-HAM's participation in implementing the mandate of the Indonesian Law on Sexual Violence in efforts to prevent and recover victims of sexual violence, as well as the challenges it faces. The findings of this research indicate that SPEK-HAM carries out several prevention and victim recovery programs by conducting awareness-raising activities and collaborating with relevant stakeholders. The obstacles encountered in these efforts include internal obstacles from within the organizers of sexual violence prevention and handling, as well as external obstacles which come from the outside.